The Maqashid Al-Sharia Ijtihad Approach and The Requirements for a Safe and Healthy Campus Free From Sexual Violence in Indonesian Universities. - Nispul Khoiri (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2021)
AbstrakThis study is a qualitative descriptive library study. The normative (usul fiqh) research method is used to examine the maqashid al-syariah ijtihad method in order to find the values that are helpful when putting together an independent and safe campus free from sexual violence in Indonesian universities. The results of this study found that an independent and healthy campus free from sexual violence is an alternative to the protection and prevention of sexual violence in the university environment in Indonesia. Strengthened through strengthening, including the commitment of the leadership, the formation of a sexual violence protection and prevention task force, conducting socialization and education on various categories of sexual violence crimes, conducting socialization and education on the importance of an independent and healthy campus from sexual violence, providing convenience and security in reporting cases, providing protection for reporters and survivors, and following up on each report. It is certain that the maslahat values found provide benefits (maintenance of religion, self, mind, property, and offspring) for the academic community. Researchers find these values through the ijtihad maqashid al-sharia method, employing istiqra' (inductive research or study) and al-ma'qul (logic) for determination.